Pengaruh Budaya Organisasi, Motivasi, Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT.PLN (Persero) Wilayah Kalimantan Selatan dan Kalimantan Tengah Area Kuala Kapuas - Eritha Sulastri; Saladin Ghalib; Taharuddin Taharuddin (Universitas Lambung Mangkurat, 2017)
This study aimed to examine the influence of organizational culture (X1), motivation (X₂), and job satisfaction (Z) the Employee Performance (Y) at PT PLN (Persero) Region South Kalimantan and Central Kalimantan area of Kuala Kapuas.The study uses a quantitative approach to the type of explanatory research. 50 employees were taken as the samples with saturated sampling technique. Data were collected with questionnaire of Likert scale level 5. The collected data were then analyzed with the use SmartPLS.The test results proved that cultural organization did not significantly affect job satisfaction, organizational culture significantly influenced employee motivation, organization culture gave significantly effects on employee performance, motivation gave significantly effects on job satisfaction, motivation did not significantly gave effects on employee performance, job satisfaction significantly gave effects on employee performance. Keywords: Organizational Culture, Motivation, Job Satisfaction, and Employee Performance